Efficient microwave absorption achieved through in situ construction of core-shell CoFe2O4@mesoporous carbon hollow spheres - Ren, Lianggui; Wang, Yiqun; Zhang, Xin; He, Qinchuan; Wu, Guanglei (International journal of minerals, metallurgy and materials, 2023)
Cobalt ferrite (CoFe 2 O 4 ), with good chemical stability and magnetic loss, can be used to prepare composites with a unique structure and high absorption. In this study, CoFe 2 O 4 @mesoporous carbon hollow spheres (MCHS) with a core-shell structure were prepared by introducing CoFe 2 O 4 magnetic particles into hollow mesoporous carbon through a simple in situ method. Then, the microwave absorption performance of the CoFe 2 O 4 @MCHS composites was investigated. Magnetic and dielectric losses can be effectively coordinated by constructing the porous structure and adjusting the ratio of MCHS and CoFe 2 O 4 . Results show that the impedance matching and absorption properties of the CoFe 2 O 4 @MCHS composites can be altered by tweaking the mass ratio of MCHS and CoFe 2 O 4 . The minimum reflection loss of the CoFe 2 O 4 @MCHS composites reaches -29.7 dB at 5.8 GHz. In addition, the effective absorption bandwidth is 3.7 GHz, with the thickness being 2.5 mm. The boosted microwave absorption can be ascribed to the porous core-shell structure and introduction of magnetic particles. The coordination between the microporous morphology and the core-shell structure is conducive to improving the attenuation coefficient and achieving good impedance matching. The porous core-shell structure provides large solid-void and CoFe 2 O 4 −C interfaces to induce interfacial polarization and extend the electromagnetic waves’ multiple scattering and reflection. Furthermore, natural resonance, exchange resonance, and eddy current loss work together for the magnetic loss. This method provides a practical solution to prepare core-shell structure microwave absorbents.